"Anesthesia for Endoscopic Carpal Tunnel Syndrome Release: A Comprehensive Systematic Review and Meta-Analysis of Local Versus Regional Versus General Anesthesia". (March 2023) - Abukhudair, Abdulrahman; Mortada, Hatan; Alhindi, Nawaf; Alarbedi, Layal; Alshehri, Abdulrahman; Alharbi, Abdullah; Kattan, Abdullah E.
Abstract: Background: Worldwide, carpal tunnel syndrome (CTS) is the most common peripheral neuropathy due to compression. A minimally invasive endoscopic carpal tunnel release (ECTR) procedure is available to treat this condition. This study aims to identify and compare the different types of anesthesia in ECTR, particularly in terms of functional outcomes, patient satisfaction, and operative time. Methods: PRISMA guideline was used to design and conduct this systematic review. MEDLINE, Cochrane, and EMBASE databases were searched systematically from inception to May 2022. For the search, MeSH terms such as ECTR, general anesthesia, local anesthesia (LA), and regional anesthesia were used. Results: As a result of reviewing the literature, 198 publications were reviewed. After implanting our criteria, 12 studies were included. We included 14589 patients who underwent ECTR. LA has a higher satisfaction rate and a shorter operative time than general anesthesia. LA had a mean operative time of 20.1 min, compared to 45 min and 51 min for regional anesthesia and general anesthesia. The number of patients with postoperative ECTR surgical complications was 2.7% (95%CI). After ECTR with LA, 95% of patients are back to their daily routine within six months. Conclusion: All the reported methods were effective, with LA being the most commonly used. Furthermore, it showed a shorter operative time and a higher satisfaction rate than other types of anesthesia. Due to the heterogeneity of the data, we recommend future randomized controlled trials to highlight the differences in anesthesia types used in ETCR. Level of evidence: III, risk/prognostic study